The effects of a soccer match on muscle damage indicators - Devrnja, Antonela; Matković, Branka (2018)
During a soccer match players perform a substantial number of explosive activities such as jumps, duels, shots and dribblings, accelerations, decelerations, changes of direction and sprints. Precisely such repetitive eccentric contractions are related to muscle damage (exercise-induced muscle damage) that is, two or three days after the match, clinically presented as muscle soreness. The aim of this research was to identify the changes in muscle damage indicators in young players after playing a soccer game. The sample of examinees was composed of 43 soccer players (16.8±1.06 years) who were divided into two groups according to their age (22 cadets aged 15.86±0.35 years and 21 U19 players aged 17.76±0.54 years). Each group played one soccer game lasting 90 minutes each. Right before and immediately after the soccer match, examinees venous blood samples were taken in order to determine the markers of muscle damage. All statistical analyses were conducted by the SPSS software. The examinees demonstrated significantly higher values of myoglobin, creatine kinase, lactate dehydrogenase, aminotransferase, alkaline phosphatase and gamma-glutamyl-transferase after the game, as well as total number of leukocytes and concentration of C-reactive protein as indicators of inflammation. The results of this research showed that, as the muscle protein concentration was increased and an inflammatory reaction also occurred, soccer matches caused muscle damage in young players.
Bibliografija: str. 119-123.
Keywords: Nogometaši -- Mišići -- Oštećenje mišića -- Kreatin-kinaza -- Leukociti